Antimicrobial-Resistance Profile of Helicobacter pylori, Obtained from Endoscopic Patients in Bahir Dar, North West Ethiopia - Mulat Erkihun; Desalegn Nigatu Chanie; Yesuf Adem Siraj (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Antimicrobial resistance for Helicobacter pylori infection is a highly emerging problem throughout the world to treat gastric-associated diseases. People living in developing countries are more likely to acquire a Helicobacter pylori infection and less likely to gate treatment after infection due to poverty. Therefore, the current study was aimed at determining the magnitude and antibiotic-resistance profile of Helicobacter pylori isolated from patients who underwent endoscopic examination. Methods. A cross-sectional study was conducted from January to May 2019 at endoscopy service-providing health facilities that are found in Bahir Dar, Ethiopia (Gamby teaching general hospital, Kidane Mihret specialty higher clinic, and Eyasta specialty higher clinic). Data were collected using a pretested, structured questionnaire. Antibiotic susceptibility of Helicobacter pylori isolates from gastric biopsies was determined. Data were analyzed using SPSS version 23. Results. The 17.8% proportion of Helicobacter pylori was isolated from 135 endoscopy-examined patients (24/135). The majority of isolates (71% of 17/24) were from males, while only 29% of 7/24) were from females. Antimicrobial-resistance of Helicobacter pylori was high to all commonly prescribed antibiotics: amoxicillin and metronidazole (91.7%), clarithromycin and ciprofloxacin (66.7% each), and tetracycline (37.5%). Conclusion. Helicobacter pylori isolates from the current study participants were rather low in number. But the highest antibiotic-resistance profile of Helicobacter pylori was observed. Therefore, these findings alarmingly indicate that routine antimicrobial susceptibility testing against Helicobacter pylori isolates is crucial for better patient management.